Aerobic Exercise Has an Effect on Forced Vital Capacity (FVC) in Collage Students - Putri Hadi Novitaningrum; Nurul Aini Rahmawati; Ali Multazam (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Currently, many students adopt an unhealthy lifestyle characterized by a lack of physical activity. Lack of physical activity can affect lung function, one of which is Forced Vital Capacity (FVC). Forced Vital Capacity (FVC) is the volume of air they can forcefully exhale when a person take a deep breath. An FVC below 80% indicates airway problems, meaning the lungs are not functioning properly. A lower FVC indicates decreased lung function, which can impact physical activity and quality of life. Aerobic exercise can improve lung function. The purpose of this study was to determine how jogging, an aerobic activity, affects FVC. This study is a quasi-experimental study using a one group pretest and posttest design Muhammadiyah Malang Physiotherapy undergraduate students who met the inclusion requirements became the research sample. The sample was measured using a spirometer before and after treatment, and they were given jogging exercises twelve times for four weeks. According to the findings of the Paired t-test, Aerobic Exercise has an effect on FVC (p-value = 0.000 < 0.05). Conclusion: based on the research results, there was an increase in FVC values ??in students after being given aerobic exercise in the form of jogging.